LEGAL ANALYSIS OF THE EFFECTIVENESS OF MEDIATION BY THE ATR/BPN OF BANYUMAS DISTRICT IN RESOLUTION OF LAND DISPUTES - Bryna Kailanajwa Hafidz (Catalist Indo Publisher, 2026)
This study aims to evaluate the effectiveness of mediation in resolving land disputes in Indonesia by examining the legal regulations governing it and the role of related institutions in the dispute resolution process. The research method used is normative juridical with statutory and conceptual approaches through the analysis of laws and regulations, policies, and mediation procedures applied in land dispute resolution. The results show that mediation is an effective alternative dispute resolution mechanism because it can reduce litigation processes that tend to be time-consuming and costly. The main legal basis for mediation is Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution. In practice, the ATR/BPN Office plays an important role as a mediator facilitator in achieving peaceful agreements between disputing parties. However, the effectiveness of mediation still faces several challenges, including the low level of public understanding regarding the benefits of mediation, the lack of good faith among disputing parties, and the limited capacity of mediators in handling disputes optimally. In conclusion, mediation has significant potential as a fast, affordable, and effective mechanism for resolving land disputes. Nevertheless, it requires improvements in mediator capacity, greater public awareness, and stronger regulations and institutional support to optimize its implementation.